Fluctuating Starvation Conditions Modify Host-Symbiont Relationship Between a Leaf Beetle and Its Newly Identified Gregarine Species - Wolz, Marina; Rueckert, Sonja; Müller, Caroline (Frontiers in Ecology and Evolution, 2022)
Gregarines are ubiquitous endosymbionts in invertebrates, including terrestrial insects. However, the biodiversity of gregarines is probably vastly underestimated and the knowledge about their role in shaping fitness-related traits of their host in dependence of fluctuating environmental conditions is limited. Using morphological and molecular analyses, we identified a new gregarine species, Gregarina cochlearium sp. n., in the mustard leaf beetle, Phaedon cochleariae. Applying a full-factorial design, we investigated the effects of a gregarine infection in combination with fluctuating starvation conditions during the larval stage on the development time and fitness-related traits of adult beetles. Under benign environmental conditions, the relationship between gregarines and the host seemed neutral, as host development, body mass, reproduction and survival were not altered by a gregarine infection. However, when additionally exposed to starvation, the combination of gregarine infection and this stress resulted in the lowest reproduction and survival of the host, which points to a parasitic relationship. Furthermore, when the host experienced starvation, the development time was prolonged and the adult females were lighter compared to non-starved individuals, independent of the presence of gregarines. Counting of gregarines in the guts of larvae revealed a lower gregarine load with increasing host body mass under stable food conditions, which indicates a regulation of the gregarine burden in dependence of the host condition. Contrary, in starved individuals the number of gregarines was the highest, hence the already weakened host suffered additionally from a higher gregarine burden. This interactive effect between gregarine infection and fluctuating starvation conditions led to an overall reduced fitness of P. cochleariae. Our study emphasises the need to study endosymbionts as important components of the natural environment and to investigate the role of host-symbiont relationships under fluctuating environmental conditions in an evolutionary and ecological context.